Health-related quality of life in patients with knee osteoarthritis attending two primary care clinics in Malaysia: a cross-sectional study - Zakaria, Zainal F.; Bakar, Azman A.; Hasmoni, Mohamed Hadzri; Abdul Rani, Mohammed Fauzi; Kadir, Salmiah A. (WONCA Global Family Doctor, 2009)
BACKGROUND: Measurement of health-related quality of life (HRQOL) among patients with osteoarthritis (OA) helps the health care provider to understand the impact of the disease in the patients' own perspective and make health services more patient-centered. The main aim of this study was to measure the quality of life among patients with symptomatic knee OA attending primary care clinic. We also aimed to ascertain the association between socio-demographic and medical status of patients with knee OA and their quality of life.